PENGARUH PROMOSI KESEHATAN TERHADAP PERUBAHAN PENGETAHUAN HIDUP BERSIH DAN SEHAT (PHBS ) PADA TATANAN RUMAH TANGGA DI DESA BATU GODANG KECAMATAN ANGKOLA SANGKUNUR TAHUN 2019 - Abdul Hamid Lubis; Ismail Efendi; Arifah Devi Fitriani (Jurnal Mutiara Kesehatan Masyarakat, 2019)
Clean and healthy living behavior is essentially the basis for preventing humans from various diseases. The initial survey in Batu Godang Village, Angkola Sangkunur District related to the PBHS indicator shows that there are still many people in Batu Godang Village who have not implemented PHBS. This study aims to analyze the effect of health promotion on changes in the behavior of Clean and Healthy Living (PHBS) on the Household Order in Batu Godang Village, Angkola Sangkunur District in 2019. When collecting data, the type of research used is quantitative with the research design Quasy-Experiment with the design of this study using one group pretest-posttest. The instrument used was an observation sheet distributed to 30 respondents. The results of data analysis showed that there was an effect of health promotion on changes in labor behavior assisted by health workers (p = 0,000). There is an effect of health promotion on changes in behavior of exclusive breastfeeding (p = 0,000). There is an effect of health promotion on changes in infant weighing behavior every month (p = 0,000). There is an effect of health promotion on changes in hand washing behavior (p = 0,000). There is an effect of health promotion on changes in the behavior of the use of clean water (p = 0,000). There is an effect of health promotion on changes in behavior of the use of healthy latrines (p = 0,000). There was an effect of health promotion on changes in behavior against mosquito larvae (p = 0,000). There is an effect of health promotion on changes in fruit and vegetable consumption behavior (p = 0,000). There is an effect of health promotion on changes in behavior in physical activity (p = 0,000). There is an effect of health promotion on changes in smoking behavior (p = 0.005). Based on the results of this study it is recommended that health workers and other health promotion providers improve PHBS behavior in the household setting and can intervene again aimed at further improving hygiene to avoid various diseases